Double‐balloon endoscopy is safe and effective for the diagnosis and treatment of small‐bowel disorders: Prospective multicenter study carried out by expert and non‐expert endoscopists in Japan. Issue 3 (13th October 2014) - Yamamoto, Hironori; Yano, Tomonori; Ohmiya, Naoki; Tanaka, Shu; Tanaka, Shinji; Endo, Yutaka; Matsuda, Tomoki; Matsui, Toshiyuki; Iida, Mitsuo; Sugano, Kentaro
<x xml:space="preserve">Abstract</x> Background and Aim Double‐balloon endoscopy (DBE) has enabled direct, detailed examination of the entire small bowel with interventional capabilities. Although its usefulness is recognized, efficacy and safety have not been extensively evaluated by prospective multicenter studies. To evaluate the efficacy and safety of DBE carried out by expert and non‐expert endoscopists, a prospective, multicenter study was conducted in five university hospitals and a general hospital in Japan. Methods A total of 120 patients who underwent 179 procedures were enrolled in the study. Experts carried out 129 procedures and non‐experts carried out 50 procedures. Primary and secondary end points were evaluation of safety, the rate of achievement of procedural objectives, namely, identification of a new lesion, detailed examination to establish a therapeutic strategy, or exclusion of significant lesions by total enteroscopy, and rate of successful examination of the entire small bowel and evaluation of safety. Results Overall rate of achievement of procedural objectives was 82.5% (99/120). Overall success rate for examination of the entire small bowel was 70.8% (34/48). Incidence of adverse events was 1.1% (a mucosal injury and an episode of pyrexia in two of 179 examinations). No severe adverse events were encountered. There were no significant differences in any of the outcome measures comparing expert and non‐expert operators. Conclusions DBE is effective and safe for patients with suspected small bowel diseases, and can be safely carried out even by a non‐expert under the supervision of an expert, following a simple training program.